Fecal Microbiota Transplantation in the Treatment of Chronic Pouchitis: A Systematic Review - Cold, Frederik; Kousgaard, Sabrina Just; Halkjaer, Sofie Ingdam; Petersen, Andreas Munk; Nielsen, Hans Linde; Thorlacius-Ussing, Ole; Hansen, Lars Hestbjerg (Microorganisms (Basel), 2020)
The objective was to evaluate available literature on treatment of chronic pouchitis with fecal microbiota transplantation (FMT) focusing on clinical outcomes, safety, and different approaches to FMT preparation and delivery. A systematic review of electronic databases was conducted using Medline, EMBASE, and the Cochrane Central Register of Controlled Trials Library from inception through April 2020. Human studies of all study types reporting results of FMT to treat chronic pouchitis were included. Nine studies, reporting FMT treatment of 69 patients with chronic pouchitis were found eligible for the review. Most studies were case series and cohort studies rated as having fair to poor quality due to high risk of bias and small sample size. Only one randomized controlled trial was included, finding no beneficial effect of FMT. In total clinical response after FMT was reported in 14 (31.8%) out of 44 evaluated patients at various timepoints after FMT, and clinical remission in ten (22.7%) patients. Only minor self-limiting adverse events were reported. FMT varied greatly regarding preparation, length of treatment, and route of delivery. The effects of FMT on symptoms of chronic pouchitis are not established, though some studies show promising results. Future controlled well-designed studies are warranted.